A Case of Multicentric Carcinoid in a Patient with Psoriatic Spondyloarthropathy. (23rd February 2015) - George, Nabil; Depala, Archana; Al Sweedan, Laith; Chakravarty, Kuntal
Abstract : We describe the first case of a patient presenting with multicentric carcinoid occurring in the lung and subsequently in the rectum, with chronic psoriatic arthritis. Although reports have been published regarding carcinoid syndrome occurring alongside rheumatoid arthritis, no reports have been made on such a case. Initial presentation of carcinoid syndrome in this patient was insidious and atypical with few symptoms, including shortness of breath and long standing abdominal bloating. Several years later a sudden change in bowel habit prompted a colonoscopy with biopsy that revealed a carcinoid rectal polyp. The case we report describes a rare presentation of carcinoid syndrome in chronic psoriatic arthropathy.